2004
DOI: 10.1007/s11664-004-0160-4
|View full text |Cite
|
Sign up to set email alerts
|

Burnout of the organic vehicle in an electrically conductive thick-film paste

Abstract: The burnout of the organic vehicle in a silver-particle, glass-free, electrically conductive, thick-film paste during firing in air was studied. For a vehicle consisting of ethyl cellulose dissolved in ether, burnout primarily involves the thermal decomposition of ethyl cellulose. The presence of ether with dissolved ethyl cellulose facilitates the burnout of ethyl cellulose. Excessive ethyl cellulose hinders the burnout. A high heating rate results in more residue after burnout. By interrupting the heating at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…These values of resistivity are similar to the resistivity of 2 Â 10 2 X cm for CZTS prepared by Nakayama and Ito [6], and larger than 0.02-0.47 X cm for CZTS obtained by both Pamplin and Feigelson [27] and Seol et al [28]. Liu and Chung [29] reported that the burnout of ethyl cellulose by itself 80% complete upon heating to 320°C and 98% complete upon heating to 475°C at a heating rate of 15°C/min. This indicated that the CZTS film sample after sintering at 400°C still contained residue ethyl cellulose, which led to its poor conductivity.…”
Section: Resultssupporting
confidence: 84%
“…These values of resistivity are similar to the resistivity of 2 Â 10 2 X cm for CZTS prepared by Nakayama and Ito [6], and larger than 0.02-0.47 X cm for CZTS obtained by both Pamplin and Feigelson [27] and Seol et al [28]. Liu and Chung [29] reported that the burnout of ethyl cellulose by itself 80% complete upon heating to 320°C and 98% complete upon heating to 475°C at a heating rate of 15°C/min. This indicated that the CZTS film sample after sintering at 400°C still contained residue ethyl cellulose, which led to its poor conductivity.…”
Section: Resultssupporting
confidence: 84%
“…We believe that the tape plays an important role in creating a thick film layer by providing a template for film formation. The resulting substrates were heated in an oven at 400°C for 2h with a heating rate of 2°C/min for binder removal [ 82 - 87 ] and cooled down to 20°C with the heating rate of 5°C/min prior to the sensing test. Finally, the Au bonding was fabricated using pure Au wires (Alfa Aesar, 0.2 mm (0.008in) dia, 99.9% (metal basis)) that were put through the tiny holes of gold electrodes by soldering.…”
Section: Methodsmentioning
confidence: 99%
“…Ethyl cellulose is thermoplastic, with a softening point of 140 °-170 °C and a melting point of 160 °-210 °C; it decomposes at temperatures above 200 °C [ 20 ] . The large exothermic peak exhibited in the thermograms of ethylcellulose and the physical mixture is attributed to ethyl cellulose decomposition [ 21 ] . The absence of an endothermic peak related to DYP melting in both the spray dried formulation and the physical mixture ( • ▶ Fig.…”
Section: Dscmentioning
confidence: 98%